PENGARUH KEDISIPLINAN DAN MOTIVASI TERHADAP KINERJA GURU DENGAN KEPUASAN KERJA SEBAGAI MEDIASI DI SMK NEGERI SUB RAYON 04 DINAS PENDIDIKAN KOTA SEMARANG (Studi Kasus Pada Guru SMK Negeri Sub Rayon 04 Kota Semarang) - 11.52.02.0085, Huriwanto (Jurnal Mahasiswa Pasca Sarjana, 2013)
This research analysis the influence of the working discipline and motivation to the teachersâ performance to with the mediation of job satisfaction at State SMK sub Rayon 04 Semarang. This research is aimed to : (1) analyze the influence of the working discipline to the job satisfaction; (2) analyze the influence of the working motivation to the job satisfaction; (3) analyze the influence of the working discipline to the teachersâ performance; (4) analyze the influence of the working motivation to the teachersâ performance; (5) analyze the influence of the job satisfaction to the teachersâ performance;The data collection of this research is using survey method and it is a population research (sensus study) which has 99 respondents. This is an explanatory research, and data analyze is using statistical analyze by the help of SPSS software for Windows Release 20.0.The results show that : (1) the working discipline has positive and significant influence to the teachersâ job satisfaction; (2) the working motivation has no significantly influence to the job satisfaction of the teacher; (3) the working discipline has positive and significant influences to the teachersâ performance; (4) working motivation has positif and significant influence to the teachersâ performance; (5) job satisfaction has positive and significant influence to the teachersâ performance; Keywords : discipline, working motivation, job satisfaction, teachersâ performance